THE SYNERGISTIC EFFECT OF GOLD NANOPARTICLE LOADED WITH CEFTAZIDIUM ANTIBIOTIC AGAINST MULTIDRUG ERSISTANCE PSEUDOMONAS AERUGINOSA - & MAHMOOD, HAMID (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to evaluate the antimicrobial activity of gold nanoparticles that was synthesized by biological method using Aloe Vera extract. The Surface morphology of the synthesized gold nanoparticles was confirmed by Atomic force microscope (AFM) while the nature of functional groups present in gold nanoparticles was determined by FT-IR analysis. The antibacterial activity of gold nanoparticle was tested against multidrug resistance (MDR)pseudomonas aeruginosa, the results showed a significant effect against MDR isolates. Gold nanoparticle was loaded with ceftazidium antibiotic in order to improve the antibacterial activity and drug delivery efficiency. The synergistic effects of biosynthesize gold loaded with ceftazidium antibiotic at different concentration against MDR bacteria were also investigated. The result showed that ceftazidium-loaded nanoparticles have superior effectiveness compared to native ceftazidium against pseudomonas aeruginosa.